Legal aspects of protecting digital entrepreneurship in the context of globalization - Ilyassova, И.С.; Satkey, Т.Б.; Zhexembayeva, Н.Е. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This article is devoted to the urgent problem of economic development of Kazakhstan, that is, the organization of digital business in private entrepreneurship. The results of the analysis of the general organizational and legal form of private entrepreneurship are presented. The main factors influencing the choice of the form of business organization are highlighted. In Kazakhstan, the features and prospects of private entrepreneurship in terms of the digitalization of the economy are clearly expressed. In addition, during the development of private entrepreneurship through a special platform, the implementation of the country's regulatory framework is not legally provided for. At the same time, using the traditional legal method, the binding nature of the current rules and the degree of their determination are determined within the framework of contractual negotiations between the parties. The study of this article revealed the absence of special legislation regulating all sectors of the economy. Instead, a specially crafted network of complex rules gives digital entrepreneurs constraints as well as opportunities. One of the signs of the relevance of this topic is that the country has been tasked with becoming one of the 30 developed countries in the world that require systematic new innovative development and accelerated technological renewal. Digital entrepreneurship has been growing rapidly in recent years, which has led, in particular, to the rapid development of technology and the Internet, the emergence of new business models, increased competition and opportunities for innovation. However, this growth posed new challenges for politicians and lawyers, who had to ensure that the legal framework and ethical position of digital entrepreneurship remained relevant and effective. The purpose of this article is to determine the prospects for the development of digital entrepreneurship in our country, and also includes a number of issues related to the protection of digital rights and the execution of digital contracts.